Hydroxyapatite coating with oxide interlayer on biomedical grade cobalt based alloy - Mas Ayu, H. (2017)
Surface modification is often required in order to improve the biological and tribological properties of metallic implants. In this research, Co-Cr-Mo alloy was oxidized in atmospheric condition to create oxide interlayer (Cr2O3) at different temperatures (850°C, 1050°C and 1250°C) for 3 hours prior to hydroxyapatite (HA) coating. The effect of oxide interlayer on the adhesion strength of HA coating on oxidized Co-Cr-Mo substrate was investigated. The surface of oxide interlayer was rough and contained abundant of pores, which helps in providing better mechanical interlocking to HA coating. Scanning electron microscopy and X-ray diffraction techniques were used to characterize the surface morphology of the HA coating whilst a Revetest scratch test was used to measure the adhesion strength of HA coating on oxidized substrates. The oxide interlayer on the substrate was able to prevent severe cracks while maintaining the porosity of the coated layer. Scratch test results showed that adhesion strength of the HA coating on substrates with interlayer was significantly higher than those without interlayer (1.40 N Vs 1.04 N; p<0.05). These findings suggest that the porous oxide interlayer provides better anchorage whilst minimizing surface cracks of HA on Co-Cr-Mo substrates. Biocompatibility test on the HA coated substrates with oxide interlayer also demonstrate strong attachment and proliferation of cells than the HA coated substrates without oxide interlayer. It is concluded that the introduction of intermediate oxide layer on Co-Cr-Mo substrate prior to HA coating has shown a positive effect in terms of increment of the adhesion strength of HA coating as well as cell bioactivity performance.